(untitled) (Polish Yearbook of International Law, 2016)
This article provides an overview of the approach taken by the International Court of Justice and its predecessor, the Permanent Court of International Justice, to questions of municipal law. Beginning with an outline of the theoretical framework, it discusses the conventional position that domestic law is a factual issue for the Court, before considering the ways in which the two Courts have utilised municipal law. It also considers to what extent the Court employs domestic law in ascertaining international legal rules.